Methods for data analysis and processing in monitoring systems of bee hives - Dineva, Kristina; Atanasova, Tatyana (Yearbook Telecommunications, 2018)
The collection, transmission, analysis and intelligent processing of collected bioprocess data is an important issue and challenge for researchers and IT specialists. Beekeeping is one of the agricultural sub-sectors where new technologies such as the Internet of Things (IoT) can be adapted and implemented successfully. Integrating data from different methods and technologies into beekeeping will improve beekeepers' knowledge of the behavior of individual bee colonies and help anticipate future events. The purpose of this article is to present a beehive monitoring system and the methods used to analyze and process collected data.